The start of schooling in the municipality of Garça/SP: aspects of school spaces: aspectos dos espaços escolares - Julião, Vania Regina Pieretti; Reis, Viviane Cássia Teixeira (Faculdade de Filosofia e Ciências, 2018)
This article presents some research results in the History of Education, centered on the History of Teacher Training developed within the scope of the Research Program "History of Teaching in Teaching Institutions in Brazil (1827-2011)" and in the group -American Journal of School and Academic Disciplines in Brazil. The object of study is the institutionalization of teacher training in the municipality of Garça SP and the school spaces as places of formation of learning. School spaces may reveal aspects of a particular education and the predominant school form. Based on the conception of school form presented by Vicent, Lahire, Thin and the notes on school spaces published by Escolano (2001) and Frago (2001), we present some aspects of the beginning of schooling in the city of Garça SP, in the first Gymnasium and School Normal instituted in the municipality. We deal with the political and social circumstances that allowed us from the constitution of the municipality to the school institutionalization as the construction of the school building, a specific space for teaching. Submission: 2018-08-28 Aceito: 2018-12-10